The Transformation of the Qurban Sacrifice from Charitable to Empowerment-Oriented: a Case Study of Cross-Border Philanthropic Collaboration in the Tebar Qurban 1447 H Program from the Perspective of Maqāṣid al-Syarīʿah - Ahmad Zaky; Abdul Gafur Arifin; Indra Indra; Tiy Kusmarrabbi; Fakhrurrozi Fakhrurrozi; Irham Dongoran (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2026)
The ritual of qurban (animal sacrifice) is frequently reduced to a charitable event in which meat is distributed and the program ends, leaving little empowerment behind. This study examines how the Tebar Qurban 1447 H program—a cross-national philanthropic collaboration between STAI As-Sunnah Deli Serdang, the Arrisalah Humanitarian Foundation (Indonesia), and the Bayaan Association (Singapore)—reconstructs qurban from a charitable model into an instrument of community empowerment. Using a qualitative instrumental case-study design, data were gathered through participant observation, documentation, and key-informant interviews across fifteen assisted villages in North Sumatra, then analyzed interactively and read through the lens of maqāṣid al-sharīʿah and Islamic philanthropy. The findings show that integrating Asset-Based Community Development with a service-learning cycle produced—at the level of process and output indicators—1,014 daʿwah-educational activities reaching 17,197 participant-visits, 21 Friday sermons attended by 1,117 worshippers, and the managed slaughter and distribution of 45 sacrificial animals across the villages. Read through maqāṣid, the program shifts the emphasis from the ritual form toward its higher objectives—social takāful, the preservation of life, and the cultivation of taqwā—positioning villagers as active subjects rather than passive recipients. The study concludes that structurally managed cross-national Islamic philanthropy can transform qurban into a sustainable vehicle of empowerment and value internalization, provided it is sustained by continued mentoring and productive follow-up